EFFECTIVENESS ASSESSMENT OF USING ENTERPRISE`S PRODUCTION AREAS AND ITS IMPACT ON PROFIT CHANGES - Коstiuk V.; Коiuda O.; Slavuta, O. (Municipal economy of cities. Series: «Economy science», 2022)
The article considers the method of modeling and factorial analysis of the company’s profit indicator. It is proposed to use deterministic mathematical profit models in the factorial analysis of this indicator, which contain a number of different factors that characterize the size, structure and efficiency of the use of the land area occupied by the enterprise. When the building of deterministic factorial system happens, it is recommended to calculate the quantitative influence on the overall change of the investigated profit indicator such important factors as the total area occupied by the analyzed enterprise, the production area on which the production process is directly carried out, the area directly occupied by the production equipment, employment rates total and production area, production output and the amount of profit per unit of the corresponding area, the level of production profitability. In order to assess the quantitative impact of these factors on the overall change of the studied profit indicator, it is suggested to carry out its step-by-step factor analysis, that is, to sequentially calculate the influence of two factors first, then three, etc. This makes it possible at each stage of the factor analysis to quickly determine the impact on the change in profit of only those factors that are the most relevant for the given enterprise at this moment in time. Factor analysis of profit is proposed to be carried out with the help of an index modification of the method of chain substitutions, which involves the use of indices of factor indicators, and not their absolute values, in analytical calculations. The relative influence of the specified factors on the overall change in profit is calculated by the ratio of the obtained absolute influence of each factor to its absolute value in the base period. The given method of modeling and factor analysis of profit makes it possible to decompose this indicator into a number of primary constituent parts, to give an analytical assessment of the impact of the efficiency of the use of production areas of the enterprise on its change, to identify the patterns of such influence, to use the information obtained to substantiate the relevant management decisions regarding the development of development tactics and strategies enterprises for the future period.